ASPEK SOSIAL EKONOMI TUMPANGSARI HUTAN DI KESATUAN PEMANGKUAN HUTAN (KPH) CIAMIS WILAYAH DAERAH ALIRAN SUNGAI (DAS) CITANDUY - Rachman Effendi; Akub J Abdurachman (Jurnal Penelitian Hasil Hutan, 1988)
One  of planting  pattern   in reforestation   that  has proved   to  be successful   is  taungya   system.   The  advantage gained by  the  farmers  are especially  in the  fulfilment  of  food  need  in  the short  term.The average income of  farmers from taungya  system  in KPH Ciamis, Citanduy  catchment area, is I47.526,- rupiahs per year per share area (0.219I hectare) or 28.5% of  farmer  total  income.Variables that significantly influence the income from taungya system  (YI)  are production facility  expenditure (XI), labour  cost  (X2),  and share area (X6).  The  relationship  is shown   by  linear regression   model YI  =  154,4588 + l,2791 XI + I,8254 X2  +  0,0214 X6  (R2 =  0,8388).Farmers  income   level  from  taungya  system   has positively  influenced  the  main  plants.  The  regression  model   that shows  the  relationship   between  farmer  income  and  base plane  area is shown   by  the  equation Y2  =  0,3557 + 0,05I3 YI   (R2 = 0,6801) at  99%  confidence   level.